A method for preparing a thermal interface material based on multi-component composite high thermal conductivity filler

By constructing an array-like network structure of boron nitride nanomaterials in thermal interface materials, the problems of poor thermal conductivity and poor processability are solved, and a multi-component thermal interface material with efficient thermal conductivity and electrical insulation are realized. In scenarios such as high-power devices and power batteries.

CN118638379BActive Publication Date: 2024-12-13SHANGHAI BORON MOMENT NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411131804.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Due to poor thermal conductivity and poor processability, thermal interface materials in existing electronic devices cannot meet the needs of efficient heat dissipation and electrical insulation, especially in application scenarios such as high-power devices and power batteries.

Method used

Using an array-like network structure based on boron nitride nanomaterials, the solid boron source is activated and dispersed alternately through ultrasonic and mechanical stirring, and the boron nitride nanotubes are grown in combination with a rotary tube furnace to build a multivariate composite high-thermal conductivity filler and through Roll-to-roll coating technology prepares thermal interface materials with isotropic and high thermal conductivity.

Benefits of technology

It achieves efficient thermal conductivity and electrical insulation, improves material processability and production efficiency, reduces costs, is suitable for heat dissipation applications of a variety of electronic components, and simplifies the structure of the thermal management system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118638379B_ABST
    Figure CN118638379B_ABST
Patent Text Reader

Abstract

A method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler relates to the technical field of a method for preparing a high thermal conductivity filler, and includes the following steps: S1: activation pretreatment of a solid boron source; S2: pretreatment of a basic filler; S3: assembly and heat treatment of a reaction precursor; S4: growth, purification and classification of boron nitride nanomaterials; S5: mother liquor slurry of a thermal interface composite phase change material; S6: continuous preparation of a thermal interface material. The present invention realizes controllable fluid viscosity during processing, which is beneficial to improving the overall thermal conductivity of the composite insulating thermal interface material, is beneficial to breaking through the mechanical performance limit existing in the prior art, is helpful to construct a stable dispersion system, is beneficial to the transmission of phonons between various phase interfaces, and thus improves the properties between different components of the composite insulating thermal interface material, can realize large-scale production of multi-component composite high thermal conductivity fillers, and helps to simplify the structure of the thermal management system while ensuring the high thermal conductivity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of a method for preparing a high thermal conductivity filler, and in particular to a method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler. Background Art

[0002] In recent years, multifunctionality and miniaturization have become the mainstream development direction of electronic devices. How to deal with the heat dissipation problem caused by the high integration of components has become one of the hot topics of the current scientific community. Designing an efficient thermal management system for high-power integrated circuits (ICs) is the core development direction of the current electronics industry. Taking electronic chips and their heat sinks / sheets (typical solid-solid interfaces) as an example, due to the roughness of the solid surface, there must be pores at the solid-solid contact interface, and these pores are filled with air with extremely poor thermal conductivity, which will lead to unsatisfactory heat transfer efficiency between the electronic chip and its heat sink / sheet; therefore, in order to achieve efficient heat dissipation of the chip, it is necessary to use high thermal conductivity materials (ie, thermal interface materials, TIMs) to fill the pores at the interface.

[0003] Current research suggests that polymer materials can be used as substrates for thermal interface materials, which can enhance the heat transfer and heat dissipation capabilities of thermal management systems for electronic devices. The main reasons for this are the following two aspects. First, on a technical level, polymers generally have excellent flexibility, which helps to fully fill the pores at the solid-solid contact position, allowing the two to fit tightly together, thereby reducing interfacial thermal resistance and achieving efficient heat transfer. Second, from the perspective of large-scale production, such materials are cost-controllable and have excellent processability, making them suitable for industrial production and applications. However, polymer materials themselves have low thermal conductivity (usually less than 0.5 Wm -1 K -1 ), in order to meet the needs of efficient heat transfer, when preparing thermal interface material terminal products, it is often necessary to add fillers with excellent thermal conductivity (usually a combination of multiple fillers, commonly used materials include metal oxides, ceramics and carbon materials), so as to establish a composite system that can meet the needs of actual application scenarios.

[0004] The latest research shows that mixing carbon nanomaterials (e.g., graphene) with low-cost conventional ceramic fillers can improve the out-of-plane thermal conductivity of polymer-based thermal interface materials while taking into account the mechanical properties of the materials; however, the thermal conductivity and mechanical properties of one-dimensional and two-dimensional nanomaterials are obviously anisotropic. For example, the in-plane thermal conductivity of graphene is much higher than its thermal conductivity in the direction perpendicular to the plane. In addition, under the action of van der Waals forces, nanomaterials with ultra-high specific surface areas will be accompanied by irreversible agglomeration during liquid phase dispersion and slurry preparation, and there are problems such as poor viscosity controllability, so their processability is not ideal. In addition, carbon nanomaterials have conductive properties and cannot be directly used in switching power supplies, high-power amplifiers, power inverters, and power batteries. The interface between conductors of different potentials (the thermal interface materials used here should have electrical insulation). Furthermore, although the graphene-based thermal interface composite material has excellent in-plane thermal conductivity, its further promotion and application are limited by its anisotropic thermal conductivity, poor processability of high-concentration slurry, and incompatibility with application scenarios that require electrical insulation. In summary, in order to meet the multi-faceted requirements of thermal interface material performance in different application scenarios and the heat dissipation problem that needs to be solved in the current development of high-power device-related industries, it is very necessary to provide a preparation method for thermal interface materials based on multi-component composite high thermal conductivity fillers. Summary of the invention

[0005] In order to overcome the drawbacks of the heat dissipation materials (thermal interface materials composed of a compound of graphene and conventional thermally conductive fillers) used in existing electronic devices due to technical limitations as described in the background technology, the present invention provides a method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler by constructing an array-like network structure based on boron nitride nanomaterials on the surface of the existing common thermally conductive filler. The prepared finished product has high thermal conductivity, strong machinability of its mother liquid slurry, and high electrical insulation properties, good thermal conductivity, and relatively high production process advantages. The application end can take into account both insulation and efficient thermal conductivity.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] A preparation method of a thermal interface material based on a multi-component composite high thermal conductivity filler, comprising the following steps, S1: activation pretreatment of a solid boron source, specifically, by alternating ultrasound and mechanical stirring for multiple times, uniformly dispersing metal nitrate substances and nano-scale solid boron sources in a certain proportion in a liquid system (the final system includes a boron source + a catalyst + some solvents, if elemental boron is used, it is insoluble), then heating and drying it in an inert atmosphere, introducing a micro-explosion reaction in the form of mechanical grinding to enhance the activity of the solid boron source, and then, by ultrasound and mixed dispersion technology, making the high-activity solid nano boron source uniformly distributed in a system with a certain viscosity (referring to The liquid system needs to have a certain viscosity (the viscosity is within 300-2700cp) to make a highly active solid boron source precursor liquid; S2: pretreatment of the basic filler, based on the application terminal requirements, select basic fillers with different diameters and diameter distributions (mix several fillers with different diameter sizes), wash them in multiple steps, and chemically functionalize and modify the filler surface to make a pretreated basic filler in order to improve the wettability of the filler surface with the medium in different systems; S3: assembly and heat treatment of the reaction precursor, a mild loading method is used in production to coat the highly active solid boron source precursor liquid on the pretreatment medium loaded with nano metal catalyst particles. The surface of the basic filler is dried to prepare a high-activity boron-nanoparticle catalyst-basic filler precursor; S4: growth, purification and classification of boron nitride nanomaterials, placing the high-activity boron-catalyst nanoparticle-basic filler precursor in a rotary tube furnace, and constructing an array-like network structure based on boron nitride nanomaterials on the surface of the basic filler by controlling the process parameters of the growth reaction, combining oxidation and chemical washing steps to remove unreacted solid boron source and catalyst nanoparticles, and after heating and drying the product in the air, the product is classified by a multi-stage cyclone separator to prepare a multi-component composite high thermal conductivity filler with a narrow particle size distribution; S5: thermal interface composite The mother liquid slurry of the phase change material specifically comprises the following steps: step 1, adding the base resin to the solvent, stirring mechanically to make it uniformly dissolved, and slowly adding the coupling agent, the tackifier and the heat stabilizer in batches during the stirring process to obtain the resin stock solution; step 2, adding the dispersant and the coupling agent to the solvent, stirring mechanically to make them uniformly dissolved, and then adding the multi-component composite high thermal conductivity filler, mixing and dispersing uniformly to obtain the filler dispersion; step 3, under stirring conditions, slowly adding the resin stock solution in step S1 in batches to the filler dispersion in step S2, and uniformly mixing, adding the defoaming agent, and standing for a certain period of time to defoam, and finally obtaining the mother liquid slurry of the thermal interface composite phase change material;S6: Continuous preparation of thermal interface materials, based on the mother liquid slurry of thermal interface composite phase change material obtained in step S5, a roll-to-roll coating machine is used to realize continuous production and preparation of polymer-based composite insulating thermal interface materials with isotropic and high out-of-plane thermal conductivity. In specific production, the coating process parameters mainly include coating speed, coating thickness and heating temperature, so that the mother liquid slurry is evenly coated on the surface of the polymer substrate through the coating unit, and then cured by drying or heating, and sent to the winding unit to prepare a roll product of thermal interface materials based on multi-component composite high thermal conductivity fillers. ;

[0008] Furthermore, in S1, metal nitrates include but are not limited to a combination of one or more of ferric nitrate, cobalt nitrate, magnesium nitrate, cadmium nitrate, aluminum nitrate, nickel nitrite, and potassium cobalt nitrite; the solid boron source includes but is not limited to a combination of one or more of elemental boron, ammonia borane, borane complex, and boric acid; the molar ratio of metal nitrates to metal elements and boron elements in the solid boron source is between 1:9-3.5:6.5; the mechanical grinding process is implemented by high-energy ball milling, and an activated gas is used for further activation during the grinding process, and the activated gas is one of ammonia and nitrogen; the viscosity of the solid boron source precursor solution is regulated by selecting different solvent systems or adding a trace amount of thickener, so that its viscosity is controlled within the range of 300-2700cp.

[0009] Furthermore, in S2, the basic filler is one or more combinations of oxides, nitrides, carbides, and borides; the organic solvents involved in the multi-step washing include but are not limited to one or more combinations of ethanol, acetone, and isopropanol, and the washing methods include immersion and ultrasonic methods; the chemical reagents used in the chemical modification are selected according to the properties of the system, including surfactants, polymers, and inorganic salts, and the modification method adopts one of mechanical ball milling, hydrothermal reaction, sol-gel, microemulsion, and co-precipitation; the system properties include organic systems and aqueous solution systems.

[0010] Furthermore, in S3, the loading method includes but is not limited to multiple impregnation-drying adsorption method, and is carried out under the protection of argon or nitrogen; the catalyst includes but is not limited to a combination of one or more of metal oxides, metal salts, and metal borides; during the rapid heating and cooling process, the rate is controlled at 35-75°C / minute; the temperature range of the in-situ reduction process is 650-850°C, the time range is 15-45 minutes, the production atmosphere is a mixture of hydrogen and nitrogen, the volume ratio of hydrogen to nitrogen is in the range of 3:97-5:85, and argon can also be used to replace nitrogen.

[0011] Furthermore, in the S4, in order to ensure the benefits of large-scale production, a feeding and discharging system with continuously adjustable speed is adopted for specific production. The process parameters include reaction temperature, reaction atmosphere, total gas flow rate, high-temperature reaction time, and rotation speed. The reaction temperature is 1030-1450°C, the reaction atmosphere includes but is not limited to a combination of one or more of ammonia, nitrogen, hydrogen, and argon, the total gas flow rate is not more than 1000sccm, the high-temperature reaction time is 0.5-3 hours, and the rotation speed of the rotary tube furnace is not more than 17 rpm; the oxidation process is carried out in air, the oxidation temperature range is 660-730°C, and the oxidation time is 6-9 hours; the chemical washing process is carried out under acidic conditions, the treatment time is 4-6 hours, the acid used includes but is not limited to nitric acid, and the chemical washing process is carried out under stirring and not exceeding 100°C.

[0012] Further, in the S5, in step one, the base resin is 0-160 parts, the coupling agent is 0.4-2 parts, the tackifier is 0.7-3 parts, the thermal stabilizer is 0-0.5 parts, the stirring speed is 500-3000 rpm, and the dissolution time is 30-200 minutes; in step two, the dispersant is 0.02-0.4 parts, the coupling agent is 0.1-0.5 parts, the multi-component composite high thermal conductive filler is 0-80 parts, the ratio of the dispersant to the solvent is 0.1-1wt%, and the solvent is 40-160 parts. The mixing and dispersion process adopts different mixing forms including ultrasonic dispersion, and ultrasonic dispersion is adopted, the frequency is 30-50kHz, the maximum power is 500W, and the ultrasonic time is 30-60 minutes; in step three, the stirring speed is 500-3000 rpm, the defoaming agent is 0.1-2 parts, and the static defoaming time is 30-200 minutes.

[0013] Furthermore, in S5, the base resin is a thermoplastic and / or thermosetting resin; thermoplastic resins include but are not limited to polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl alcohol, polystyrene, polyamide, polyimide, and thermosetting resins include but are not limited to epoxy resins, phenolic resins, and polyurethane; the base resin can also be selected from composite matrix materials, including but not limited to one or more of phenolic-nitrile, phenolic-polyurethane, and epoxy-nitrile.

[0014] Furthermore, in S5, the multi-component composite high thermal conductivity filler can be a compound of a variety of different materials, shapes and sizes (several fillers with different diameters, sizes and shapes are mixed in a multi-component manner), and each type of filler has different morphological characteristics. The use of a multi-component filler system is helpful to construct an isotropic three-dimensional thermal conductive path, and quickly conduct the heat generated at the heat source to the heat sink in all directions, thereby achieving the purpose of efficient heat transfer; at the same time, the ratio of various types of thermal conductive fillers in the mother liquid slurry is adjusted according to actual needs, thereby regulating the processability of the slurry, and the processability includes but is not limited to viscosity.

[0015] Furthermore, in S5, the dispersant includes but is not limited to one or more of sodium dodecylbenzene sulfonate, stearic acid, fatty acid glyceride, amino acid surfactant, polyvinyl pyrrolidone, and polyoxyethylene ether. The dispersant is used to modify the surface of the filler so that it can be evenly dispersed in the entire system, thereby enhancing the interaction between the filler and the base resin, reducing the interfacial thermal resistance between different components, and at the same time obtaining a mother liquid slurry with uniform components and stable structure.

[0016] Furthermore, in S5, the coupling agent includes but is not limited to one or more of silane coupling agents, titanate esters, and aluminate coupling agents. The coupling agent is used to improve the interaction between the polymer material and the multi-filler, enhance the interface bonding strength, and reduce the interface thermal resistance, thereby improving the overall thermal conductivity and mechanical strength of the composite material after molding.

[0017] Furthermore, in S5, the defoaming agent is one of silicon, alkane and mineral oil. The defoaming agent performs defoaming through one or more of the following mechanisms and has the following main functions: destroying the elasticity of the foam film, reducing the local surface tension of the foam, promoting the drainage of the liquid film, and solubilizing the surfactant; the thickener includes but is not limited to one or more of polyborosiloxane and carboxymethyl cellulose. The thickener is used to regulate the fluidity of the material after heating to avoid problems such as excessive fluidity and difficulty in processing after the material softens.

[0018] Furthermore, in S5, the heat stabilizer includes but is not limited to one or more of stearates, aromatic amine compounds, phosphites, and hydroxylamine compounds, and the stearate is one of calcium stearate, zinc stearate, and barium stearate; the type and amount of the heat stabilizer are selected according to the polymer base resin in the actual application scenario to avoid or slow down thermal degradation of the polymer; the solvent includes but is not limited to one or more of water, ethanol, acetone, N-methylpyrrolidone, dimethylformamide, and dimethyl sulfoxide, and the solvent needs to be selected according to the main ingredients and auxiliary materials used to promote uniform mixing of the components.

[0019] Furthermore, in S6, the coating speed is not greater than 10 m / min, the coating thickness is 0.03-2.5 mm, and the heating temperature is not higher than 140°C.

[0020] Compared with the prior art, the invention has the following advantages: the product prepared by the invention can be directly used for heat dissipation of electronic components in industries such as computers, electrical and electronic, telecommunications, automobiles, photovoltaic cells, etc. (installed between the heating surface of the electronic component and the radiator), and has the following advantages. (1) The goal of controlling the fluid viscosity during processing and constructing a three-dimensional thermal conductive path is achieved, which is conducive to solving the problem of anisotropy of thermal conductivity caused by the use of a single morphology filler; (2) Compared with the existing simple mixed filler process, the interaction force between the multi-filler particles is stronger and the thermal resistance is smaller, which is more conducive to improving the overall thermal conductivity of the composite insulating thermal interface material; (3) It is conducive to breaking through the mechanical performance limits existing in the existing technology; at the same time, it reduces product costs and improves processability, with the advantages of reducing costs and increasing efficiency; (4) It helps to build a stable dispersion system, which is conducive to the transmission of phonons between phase interfaces, thereby improving the performance of different components of the composite insulating thermal interface material; (5) It can realize large-scale production of multi-composite high thermal conductivity fillers; (6) The prepared composite coating uses a series of electrically insulating materials. While ensuring the high thermal conductivity of the material, it is widely compatible with usage scenarios with insulation requirements, which helps to simplify the structure of the thermal management system. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention provides a process technology roadmap for the preparation of a thermal interface material based on a multi-component composite high thermal conductivity filler.

[0022] Figure 2 It is a thermal conductivity theoretical model diagram of the preparation method of the thermal interface material based on the multi-component composite high thermal conductivity filler of the present invention.

[0023] Figure 3 This is a scanning electron microscope image of the pretreated basic filler (spherical alumina) after washing prepared in Example 1 of the present invention.

[0024] Figure 4 This is a scanning electron microscope image of a one-dimensional boron nitride nanotube (catalyst precursor: ferric nitrate nonahydrate) prepared by a heat treatment annealing process in each Example 1 of the present invention.

[0025] Figure 5 This is a scanning electron microscope image of the array-like network structure based on boron nitride nanotubes constructed on the surface of the basic filler in Example 1 of the present invention.

[0026] Figure 6 This is a scanning electron microscope image of the multi-component composite high thermal conductive filler in Example 1 of the present invention.

[0027] Figure 7 This is the test result of the transient plane hot plate method for the composite thermal interface material prepared in Example 1 of the present invention.

[0028] Figure 8 This is a scanning electron microscope image of the pretreated basic filler (quasi-spherical boron nitride) after washing prepared in Example 2 of the present invention.

[0029] Fig. 9 This is a scanning electron microscope image of the one-dimensional boron nitride nanotube (catalyst precursor: ferric nitrate nonahydrate and cobalt nitrate hexahydrate) prepared by the heat treatment annealing process in each Example 2 of the present invention.

[0030] Fig.10 This is a scanning electron microscope image of the multi-component composite high thermal conductive filler in Example 2 of the present invention.

[0031] Fig.11 1 is a curve showing the relationship between the temperature change (detector signal) of different thermal interface materials and time during the heating and cooling process in Example 2 of the present invention.

[0032] Fig.12 The relationship between the surface temperature of the solar cell without thermal interface composite phase change material, containing thermal interface composite phase change material (without multi-composite high thermal conductivity filler) and containing thermal interface composite phase change material (with multi-composite high thermal conductivity filler) inside the photovoltaic module collector in Example 3 of the present invention during a day. DETAILED DESCRIPTION

[0033] Embodiment 1, Figure 1As shown, a preparation method of a thermal interface material based on a multi-component composite high thermal conductivity filler for use between a vehicle power battery and a cooling tube (air cooling or liquid cooling) includes the following process. (1) Ferric nitrate nonahydrate and nano-sized elemental boron powder (the molar ratio of iron element to boron element is 1.5:8.5) are uniformly dispersed in ethanol by alternating ultrasonic and mechanical stirring for multiple times; further, after drying under an inert atmosphere (heating), high-energy ball milling is performed (the atmosphere of the ball milling process is set to pure ammonia, the pressure is 320kpa, and the ball milling time is 144 hours) to introduce a micro-explosion reaction (there are metal elements, nitrates and solid boron raw materials in the system, which can be considered as a fuel) to enhance the activity of the solid boron source; further, by centrifugal dispersion technology, the high-activity solid nano boron source is uniformly distributed in glycerol to prepare a high-activity solid boron source precursor solution. (2) Spherical alumina is selected as a basic filler, and ultrasonic washing is performed twice in a mixed solution of ethanol and deionized water and acetone; a pre-treated basic filler is prepared. (3) In an argon atmosphere, the immersion (immersing the pretreated base filler in an ethanol solution of ferric nitrate nonahydrate)-drying process is repeated three times to further introduce ferric nitrate onto the surface of the pretreated base filler; further, the ferric nitrate in the system is reduced to nano-iron particles by a rapid heating-cooling process (temperature change rate of 55°C / min, reduction temperature of 750°C, reduction time of 15 minutes, and atmosphere of 5% argon-hydrogen mixture), and the particles are firmly dotted onto the surface of the pretreated base filler; further, a high-activity solid boron source precursor liquid is sprayed onto the surface of the pretreated base filler loaded with nano-iron catalyst particles, and dried to prepare a high-activity boron-nano-iron particle catalyst-base filler precursor. (4) The above-mentioned high-activity boron-catalyst nanoparticle-base filler precursor is placed in a rotary tube furnace, and by controlling the reaction temperature (1150°C) of the growth reaction, the reaction atmosphere (a mixture of nitrogen and hydrogen in a ratio of 90:10), the total gas flow rate (400sccm), the high-temperature reaction time (1.5 hours), and the rotary furnace speed (2 rpm), a quasi-array network structure based on boron nitride nanotubes is constructed on the surface of the base filler; further, the unreacted solid boron source and metallic iron nanoparticles are removed by combining oxidation (air atmosphere, 670°C, 7 hours) and nitric acid washing (accompanied by heating and stirring at a temperature of 80°C); further, after the product is dried in air, it is classified by a multi-stage cyclone separator to prepare a multi-component composite high thermal conductive filler with uniform particle size.(5) Take polyvinyl alcohol resin (160 parts), heat it to 75°C and stir it mechanically; during the stirring process, slowly add silane coupling agent (1.5 parts) in batches (speed is 700-1200 rpm, and the mixing process time is 150-200 minutes) to prepare a resin stock solution; further, add sodium dodecylbenzene sulfonate (0.2 parts) and silane coupling agent (0.5 parts) into water and stir them mechanically to mix them evenly; the ratio of sodium dodecylbenzene sulfonate to water is 0.1wt / v; add the above-mentioned multi-component composite high thermal conductive filler based on boron nitride nanotubes (40 parts), mix them centrifugally, and prepare a filler dispersion; further, under stirring conditions (speed is 700-1200 rpm), slowly add the resin stock solution to the filler dispersion in batches, mix them evenly, add fatty acid ester (2 parts), let it stand for defoaming (70 minutes), and obtain a mother liquor slurry containing multi-component composite high thermal conductive filler. (6) Based on the mother liquid slurry containing the multi-component composite high thermal conductivity filler, a roll-to-roll coating machine is used to control its coating speed (7 m / min), coating thickness (2.0 mm), and heating temperature (100°C), so that the mother liquid slurry is evenly coated on the surface of the polymer substrate (polyethylene terephthalate) through the coating unit, and then cured by drying or heating, thereby realizing continuous production of a polymer-based composite insulating thermal interface material with isotropic and high out-of-plane thermal conductivity.

[0034] In this embodiment 1, there is no nanomaterial attached to the surface of the pre-treated base filler after ultrasonic washing with a mixed solution of ethanol and deionized water and acetone ( Figure 3 ); The diameter of the one-dimensional boron nitride nanotubes prepared by the heat treatment annealing process is 40-100 nanometers and the length is 10-50 microns ( Figure 4 The microscopic morphology of the multi-component composite high thermal conductive filler shows that there are boron nitride nanotubes with an array-like network structure on the surface of the basic filler ( Figure 5 ), which is conducive to the construction of an effective three-dimensional thermal conductive path inside the thermal interface material, that is, spherical alumina fillers (particle diameter is about 600 microns, Figure 6 ) is easier to form an isotropic heat conduction path under low load conditions; experimental comparison tests show that compared with adding only basic filler (spherical alumina), the material using multi-component composite high thermal conductivity filler has higher isotropic thermal conductivity performance (4.458 VS 19.790 W m -1 K -1 , Figure 7 ).

[0035] Embodiment 2, Figure 1As shown, a preparation method of a thermal interface material based on a multi-component composite high thermal conductivity filler for filling between a chip integrated circuit (IC) and a heat dissipation cover includes the following process. The preparation path of the polymer-based composite insulating thermal interface material and the multi-component composite high thermal conductivity filler used in this embodiment is as follows. (1) Cobalt nitrate hexahydrate, iron nitrate nonahydrate and nano-scale elemental boron powder (the molar ratio of cobalt, iron and boron elements is 1.0:1.0:8.0) are uniformly dispersed in ethanol by alternating ultrasonic and mechanical stirring for multiple times; further, after drying (heating) under an inert atmosphere, high-energy ball milling is performed (the atmosphere of the ball milling process is set to pure ammonia, the pressure is 300kpa, and the ball milling time is 144 hours) to introduce a micro-explosion reaction and enhance the activity of the solid boron source; further, the high-activity solid nano-boron source is uniformly distributed in glycerol through centrifugal dispersion technology to prepare a high-activity solid boron source precursor solution. (2) Selecting a spherical hexagonal boron nitride assembly as a basic filler, gently rinsing it twice in a mixed solution of ethanol and deionized water (preferably accompanied by mechanical stirring); preparing a pretreated basic filler. (3) Repeating the immersion (immersing the pretreated basic filler in an ethanol solution of cobalt nitrate hexahydrate)-drying process three times in a nitrogen atmosphere, further introducing iron nitrate on the surface of the pretreated basic filler; further, reducing the iron nitrate and cobalt nitrate in the system to nano-iron and nano-cobalt particles respectively through a rapid heating-cooling process (temperature change rate of 50°C / min, reduction temperature of 730°C, reduction time of 25 minutes, atmosphere of 5% argon-hydrogen mixed gas), and firmly embellishing the surface of the pretreated basic filler; further, spraying a high-activity solid boron source precursor liquid on the surface of the pretreated basic filler loaded with nano-iron and nano-cobalt catalyst particles, and drying it, to prepare a high-activity boron-nano-iron-nano-cobalt particle catalyst-basic filler precursor. (4) The above-mentioned high-activity boron-catalyst nanoparticle-base filler precursor is placed in a rotary tube furnace, and by controlling the reaction temperature (1180°C) of the growth reaction, the reaction atmosphere (a mixture of nitrogen and ammonia in a ratio of 70:30), the total gas flow rate (500sccm), the high-temperature reaction time (3 hours), and the rotary furnace speed (2.5 rpm), a quasi-array network structure based on boron nitride nanotubes is constructed on the surface of the base filler; further, by combining oxidation (air atmosphere, 670°C, 7 hours) and nitric acid washing (accompanied by heating and stirring at a temperature of 80°C) steps, unreacted solid boron source and metallic iron and metallic cobalt nanoparticles are removed; further, after the product is dried in air, it is classified by a multi-stage cyclone separator to prepare a multi-component composite high thermal conductive filler with uniform particle size.(5) Take epoxy resin (100 parts), heat to 65°C and stir mechanically; during the stirring process, slowly add sodium cholate (0.25 parts) and silane coupling agent (0.5 parts) in batches (rotation speed is 2500-3000 rpm, and the mixing process time is 120-150 minutes) to prepare a resin stock solution; further, add sodium dodecylbenzene sulfonate (0.2 parts) and silane coupling agent (0.5 parts) into water and stir mechanically to make them evenly mixed; The ratio of sodium dialkylbenzene sulfonate and water is 0.1wt / v; the above-mentioned multi-component composite high thermal conductivity filler based on boron nitride nanotubes (100 parts) is added, and centrifugal mixing is performed to prepare a filler dispersion; further, under stirring conditions (speed of 700-1200 rpm), the resin stock solution is slowly added to the filler dispersion in batches and evenly mixed, and fatty acid ester (1.5 parts) is added, and the mixture is allowed to stand for defoaming (70 minutes) to obtain a mother liquid slurry containing a multi-component composite high thermal conductivity filler. (6) Based on the mother liquid slurry containing a multi-component composite high thermal conductivity filler, a roll-to-roll coating machine is used to control its coating speed (6 m / min), coating thickness (1.8 mm), and heating temperature (90°C), so that the mother liquid slurry is evenly coated on the surface of a polymer substrate (polyethylene terephthalate) through a coating unit, and then cured by drying or heating, so as to realize continuous production and preparation of a polymer-based composite insulating thermal interface material with isotropic and high out-of-plane thermal conductivity.

[0036] Example 2 The materials in each link of the preparation process of this example were characterized by a method similar to that of Example 1. After washing with a mixed solution of ethanol and deionized water, there was no nanomaterial attached to the surface of the pretreated basic filler, and the diameter was 10-40 microns ( Figure 8 ); The diameter of the one-dimensional boron nitride nanotubes prepared by heat treatment annealing process is 50-150 nanometers and the length is 10-50 microns ( Fig. 9 ); The array-like arrangement of boron nitride nanotubes on the surface of the basic filler in the multi-component high thermal conductivity filler helps to build an effective three-dimensional thermal conductive path inside the thermal interface material ( Fig.10 ); Experimental comparative tests have shown that compared with adding only basic filler (spherical alumina), the material using multi-component composite high thermal conductivity filler has higher isotropic thermal conductivity (4.46 VS 27.45 W m -1 K -1 In addition, under the same heating conditions, the polymer-based composite insulating thermal interface material containing multi-component composite high thermal conductivity fillers has better heat dissipation capacity ( Fig.11 ).

[0037] Embodiment 3, Figure 1As shown, a preparation method of a thermal interface material based on a multi-component composite high thermal conductivity filler for filling the inside of a collector equipped with metal fins in a photovoltaic module includes the following process. (1) Cobalt nitrate hexahydrate and nano-sized elemental boron powder (the molar ratio of cobalt element to boron element is 2.5:7.5) are uniformly dispersed in ethanol by alternating ultrasonic and mechanical stirring for multiple times; further, after drying (heating) under an inert atmosphere, high-energy ball milling is performed (the atmosphere of the ball milling process is set to pure ammonia, the pressure is 300kpa, and the ball milling time is 144 hours) to introduce a micro-explosion reaction to enhance the activity of the solid boron source; further, the high-activity solid nano boron source is uniformly distributed in glycerol by centrifugal dispersion technology to prepare a high-activity solid boron source precursor solution. (2) The spherical hexagonal boron nitride assembly is selected as the basic filler, and is gently rinsed twice in a mixed solution of ethanol and deionized water (preferably accompanied by mechanical stirring); and the pre-treated basic filler is prepared. (3) In a nitrogen atmosphere, the immersion (immersing the pretreated base filler in an ethanol solution of ferric nitrate nonahydrate)-drying process is repeated three times to further introduce ferric nitrate on the surface of the pretreated base filler; further, the cobalt nitrate and ferric nitrate in the system are reduced to nano-cobalt and nano-iron particles respectively through a rapid heating-cooling process (temperature change rate of 60°C / min, reduction temperature of 730°C, reduction time of 25 min, atmosphere of 5% argon-hydrogen mixture), and the nano-iron particles are firmly dotted on the surface of the pretreated base filler; further, a high-activity solid boron source precursor liquid is sprayed on the surface of the pretreated base filler loaded with nano-cobalt and nano-iron catalyst particles, and dried to prepare a high-activity boron-nano-cobalt-nano-iron particle catalyst-base filler precursor. (4) The above-mentioned high-activity boron-catalyst nanoparticle-base filler precursor is placed in a rotary tube furnace, and by controlling the reaction temperature (1180°C) of the growth reaction, the reaction atmosphere (a mixture of nitrogen and ammonia in a ratio of 70:30), the total gas flow rate (500sccm), the high-temperature reaction time (3 hours), and the rotary furnace speed (2.5 rpm), a quasi-array network structure based on boron nitride nanotubes is constructed on the surface of the base filler; further, the unreacted solid boron source and residual metal nanoparticles are removed by combining oxidation (air atmosphere, 670°C, 7 hours) and nitric acid washing (accompanied by heating and stirring at a temperature of 80°C); further, after the product is dried in air, it is classified by a multi-stage cyclone separator to prepare a multi-component composite high thermal conductive filler with uniform particle size.(5) Take 100 parts of thermal phase change material (including 80 parts of capric acid and 20 parts of palmitic acid) and heat it to 40°C, and make it in a uniform molten state by mechanical stirring; during the stirring process, slowly add silane coupling agent (1.2 parts) in batches (the rotation speed is 2000-2500 rpm, and the mixing process time is 150-180 minutes) to prepare a resin stock solution containing thermal phase change material (preferably, it can be cooled to solidify and shape it to obtain a solid thermal interface composite phase change material precursor). Further, sodium cholate (0.15 parts) and silane coupling agent (0.3 parts) are added to ethanol and mechanically stirred to uniformly mix; the ratio of sodium cholate to ethanol is 0.1wt / v; then the above-mentioned multi-component composite high thermal conductivity filler (total amount: 13 parts) is added, centrifugally mixed, and a filler dispersion is prepared; further, under stirring conditions (rotation speed of 2000-2500 rpm), the above-mentioned solid thermal interface composite phase change material precursor is slowly added to the above-mentioned filler dispersion in batches for uniform mixing to obtain a mother liquor slurry containing multi-component composite high thermal conductivity filler and thermal phase change material. (6) Based on the mother liquid slurry containing multi-component composite high thermal conductivity filler, a roll-to-roll coating machine is used to control its coating speed (5 m / min), coating thickness (1.6 mm), and heating temperature (50°C), so that the mother liquid slurry is evenly coated on the surface of the polymer substrate (polyethylene terephthalate) through the coating unit, and then solidified after drying and cooling to achieve continuous production and preparation of a polymer-based composite insulating thermal interface material with isotropic and high out-of-plane thermal conductivity. (7) The above polymer-based composite insulating thermal interface material is transferred to the surface inside the collector equipped with metal fins in the photovoltaic module, and the composite phase change material in the above thermal interface material is converted into a molten state by an external heat source to achieve solid-solid bonding; in actual working conditions, the temperature of the solar photovoltaic panel is controlled to operate within the optimal operating temperature range.

[0038] Example 3 uses a method similar to that of Example 2 to characterize the materials in each link of the preparation process of this example. The results show that the raw materials and the prepared multi-component composite high thermal conductivity filler are similar to the corresponding substances in Example 2. The experimental comparison test found that the thermal conductivity of the composite phase change material containing and not containing thermal conductive filler is 0.33 W m -1 K -1 and 17.98 W m -1 K -1 (The thermal conductivity of the composite phase change material without thermal conductive filler is 0.11 W m -1 K -1); Thermal analysis tests (differential thermal analysis (DTA) and differential scanning calorimetry (DSC)) were conducted on the material, and its phase change latent heat and phase change temperature were 47.01 kJ / kg and 21.9°C respectively; experimental comparative tests found that under the same climatic conditions, the surface temperature of the photovoltaic module with thermal interface composite phase change material with boron nitride thermal conductive filler inside the metal fin collector was the lowest during the monitoring time, indicating that the material is conducive to improving the device's temperature control and heat dissipation capabilities ( Fig.12 ).

[0039] Through the above ( Figure 1As shown), the present invention loads the catalyst on the surface of the pretreated basic filler, and through an in-situ reduction reaction, it is dotted on the filler surface in the form of nano-metal particles; then a high-activity solid boron source precursor liquid is coated thereon and dried; a high-temperature annealing reaction is then performed to grow boron nitride nanomaterials on the surface of the filler, and after purification and classification, a multi-component composite high thermal conductivity filler with a certain particle size (narrow particle size distribution) is prepared; finally, the mother liquid of the thermal interface material is prepared based on the multi-component composite high thermal conductivity filler, and a polymer-based composite insulating thermal interface material is prepared by introducing a roll-to-roll technology suitable for large-scale production. The present invention aims at the shortcomings of the prior art (thermal interface materials composed of a composite of multi-fillers, i.e., graphene and conventional thermally conductive fillers), and on this basis, proposes a strategy of optimizing process equipment, auxiliary materials and production routes, i.e., using the above-mentioned fillers with a lower solid content, and using a high-temperature rotary furnace combined with a roll-to-roll film process to prepare a polymer-based composite insulating thermal interface material with isotropic and high out-of-plane thermal conductivity in large quantities, so that the prepared composite insulating thermal interface material has high (isotropic) thermal conductivity, strong processability of its mother liquid slurry, and electrical insulation properties. The thermal interface material prepared by using a basic filler with a surface modified with an electrically insulating array-like boron nitride nanomaterial is conducive to overcoming the problems of existing thermal conductive materials in performance (thermal conductivity anisotropy), production process (unsatisfactory processability of the mother liquid slurry, low production efficiency), and application end (unable to take into account the use scenarios that require insulation and high-efficiency thermal conductivity, such as thermal interface materials used between conductors of different potentials). Specifically, the advantages of the present invention are summarized as follows: (1) By using a variety of multi-component composite high thermal conductivity fillers of different materials, shapes and sizes, the goal of controllable fluid viscosity during processing and the construction of a three-dimensional thermal conductive path can be achieved, which is conducive to solving the problem of anisotropy of thermal conductivity caused by the use of a single morphology filler. (2) Boron nitride nanomaterials (boron nitride nanotubes and / or nanosheets) are directly grown on the surface of the basic filler by in-situ growth; compared with the simple mixed filler process, the interaction force between the multi-component filler particles is stronger, the thermal resistance is smaller, and it is more conducive to improving the overall thermal conductivity of the composite insulating thermal interface material. (3) The boron nitride nanomaterial grown on the surface of the basic filler in the present invention has an array-like network structure, which can reduce the total amount of thermal conductive filler added while ensuring the good thermal conductivity of the composite material, which is conducive to breaking through the mechanical performance limits existing in the prior art; at the same time, it reduces product costs and improves processability (making it compatible with a variety of coating processes, including but not limited to roll-to-roll, spraying, and brushing processes), and has the advantages of reducing costs and increasing efficiency ( Figure 2). (4) The surface modification of the base resin and the multi-component composite high thermal conductivity filler is carried out by coupling agent and dispersant respectively, which increases the compatibility between different components, helps to build a stable dispersion system, and is beneficial to the transfer of phonons between phase interfaces (by inhibiting phonon scattering at the interface), thereby improving the performance of different components of the composite insulating thermal interface material (i.e., improving mechanical strength and reducing thermal resistance). (5) The production processes involved all adopt a continuous system, including a high-temperature rotary reactor and a roll-to-roll film process, which can achieve large-scale production of multi-component composite high thermal conductivity fillers (annual output of more than 12 tons per production line) and corresponding polymer-based composite insulating thermal interface materials (annual output of more than 500,000 square meters per equipment). (6) The prepared composite coating uses a series of electrically insulating materials. While ensuring the high thermal conductivity of the material, it is widely compatible with usage scenarios with insulation requirements (such as surface heat dissipation coatings on printed circuit boards), which helps to simplify the structure of the thermal management system. In general, by constructing a quasi-array network structure based on boron nitride nanomaterials on the surface of conventional thermal conductive fillers, and by regulating the components and optimizing the structure (including the composition, size, morphology and dosage of the multi-fillers used) and improving the process equipment and production routes, a set of systems for mass production is established, which enables the ability to prepare low-cost, isotropic thermal conductive materials (with high out-of-plane thermal conductivity) and highly processable composite insulating thermal interface materials. In compatible with usage scenarios that require electrical insulation, technological innovation in related fields is promoted and market expansion is driven by cost reduction and efficiency improvement.

[0040] In the present invention, Figure 3 In the figure, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; LM is low magnification; UL is high and low detectors; μm is micrometer. Figure 4 In the table, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; k is thousand; SE is secondary electron; UL is high-level and low-level detectors; μm is micrometer. Figure 5 In the figure, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; k is thousand; LM is low magnification; UL is high and low detectors; μm is micrometer. Figure 6 In the figure, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; LM is low magnification; UL is high-level and low-level detectors. Figure 8 In the figure, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; LM is low magnification; UL is high and low detectors; μm: micrometer. Fig. 9 In the table, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; k is thousand; SE is secondary electron; UL is high-level and low-level detectors; μm is micrometer. Fig.10In the figure, Regulus is the scanning electron microscope model; kV is kilovolt; mm is millimeter; k is thousand; SE is secondary electron; UL is high and low detectors; μm is micrometer. The preparation mechanism of high-activity boron-nanoparticle catalyst-basic filler precursor is as follows: in the system (including boron source + catalyst + some solvents), metal nitrate substances have strong oxidizing properties. During the mechanical grinding process, they will burn and explode when encountering organic solvents, thereby increasing the activity of the nano-scale solid boron source, so that it can form a "high-activity boron-solvent" (B x N y -Solvent); further, the "highly active boron-solvent" (B x N y -Solvent) precursor. On the other hand, a catalyst is further introduced on the surface of the pre-treated base filler to form a "base filler-metal ion". The "metal ion" (M n+ ) is reduced to "nano-metal catalyst particles" (nano-M, i.e., catalyst) to obtain the product "basic filler-nano-metal catalyst particles" (nano M@filler); finally, "highly active boron-solvent" (B x N y -Solvent) is coated on the surface of "basic filler-nanometal catalyst particles", and after drying and removing the solvent, particles of "highly active boron-basic filler-nanometal catalyst particle precursor" are formed (B x N y -nano M@filler).

[0041] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0042] In addition, it should be understood that although the present specification is described according to the implementation mode, the implementation mode does not only include an independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in the embodiments can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler, characterized in that: The method comprises the following steps: S1: pretreatment of solid boron source activation, specifically, by alternating ultrasonic and mechanical stirring for multiple times, uniformly dispersing metal nitrate substances and nano-scale solid boron source in a certain proportion in a liquid system, then heating and drying them in an inert atmosphere, introducing micro-explosion reaction in the form of mechanical grinding, enhancing the activity of the solid boron source, and making the high-activity solid nano boron source uniformly distributed in a system with a certain viscosity through ultrasonic and mixed dispersion technology to prepare a high-activity solid boron source precursor liquid, the mechanical grinding process is implemented by high-energy ball milling, and activation gas is used for further activation during the grinding process, and the activation gas is ammonia; S2: pretreatment of basic filler, specifically based on the application terminal requirements, selecting different diameters and straight The base filler with a diameter distribution is washed in multiple steps to prepare a pre-treated base filler; S3: assembly and heat treatment of reaction precursors, in which a loading method is adopted in production, a high-activity solid boron source precursor liquid is coated on the surface of the pre-treated base filler loaded with nano-metal catalyst particles, and dried to prepare a high-activity boron-nano particle catalyst-base filler precursor, wherein the nano-metal catalyst particles are nano-iron; the metal nitrates include one or a combination of iron nitrate and cobalt nitrate; the solid boron source includes one or a combination of elemental boron, ammonia borane, borane complex, and boric acid; the molar ratio of the metal nitrate to the metal element and the boron element in the solid boron source is between 1:9 and 3.5:6.5; S4: boron nitride nanoparticles The growth, purification and classification of rice materials, placing a high-activity boron-catalyst nanoparticle-basic filler precursor in a rotary tube furnace, constructing an array-like network structure based on boron nitride nanomaterials on the surface of the basic filler by controlling the process parameters of the growth reaction, combining oxidation and chemical washing steps to remove unreacted solid boron source and catalyst nanoparticles, heating and drying the product in the air, and then classifying the product through a multi-stage cyclone separator to prepare a multi-component composite high thermal conductive filler with a narrow particle size distribution; S5: thermal interface composite phase change material mother liquor slurry, specifically including the following steps, step one, adding the base resin to the solvent, mechanically stirring it to make it evenly dissolved, and during the stirring process, slowly adding the coupling agent and the thickener in batches and a thermal stabilizer to obtain a resin stock solution, in step two, adding a dispersant and a coupling agent to a solvent, mechanically stirring to dissolve them evenly, and then adding the multi-component composite high thermal conductivity filler, mixing and dispersing them evenly to obtain a filler dispersion, in step three, under stirring conditions, slowly adding the resin stock solution in step S1 in batches to the filler dispersion in step S2, and mixing them evenly, adding a defoaming agent, standing and defoaming for a certain period of time, and finally obtaining a thermal interface composite phase change material mother liquid slurry; S6: continuous preparation of thermal interface materials, based on the thermal interface composite phase change material mother liquid slurry obtained in step S5, a roll-to-roll coater is used to realize continuous production and preparation of polymer-based composite insulating thermal interface materials with isotropic and high out-of-plane thermal conductivity.

2. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S1, the viscosity of the solid boron source precursor solution is regulated by selecting different solvent systems or adding a trace amount of thickener, so that the viscosity is controlled within the range of 300-2700cp.

3. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S2, the basic filler is one or more combinations of oxides, nitrides, carbides, and borides; the organic solvents involved in the multi-step washing include one or more combinations of ethanol, acetone, and isopropanol, and the washing methods include immersion and ultrasonic methods.

4. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S3, the loading method is selected as a multiple impregnation-drying adsorption method, and is carried out under the protection of argon or nitrogen.

5. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S4, the specific production adopts a feeding and discharging system with continuously adjustable speed, and the process parameters include reaction temperature, reaction atmosphere, total gas flow rate, high temperature reaction time, and rotation speed. The reaction temperature is 1030-1450°C, the reaction atmosphere includes a combination of one or more of ammonia, nitrogen, hydrogen, and argon, the total gas flow rate is not more than 1000sccm, the high temperature reaction time is 0.5-3 hours, and the rotation speed is not more than 17 rpm; the oxidation process is carried out in air, the oxidation temperature range is 660-730°C, and the oxidation time is 6-9 hours; The chemical washing process is carried out under acidic conditions for 4-6 hours. The acid used is nitric acid. The chemical washing process is carried out under stirring and at a temperature not exceeding 100°C.

6. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: S5, in step one, the base resin is 100-160 parts, the coupling agent is 0.4-2 parts, the tackifier is 0.7-3 parts, the thermal stabilizer is 0-0.5 parts, the stirring speed is 500-3000 rpm, and the dissolution time is 30-200 minutes; in step two, the dispersant is 0.02-0.4 parts, the coupling agent is 0.1-0.5 parts, the multi-component composite high thermal conductive filler is 13-80 parts, the ratio of dispersant to solvent is 0.1-1wt%, and the solvent is 40-160 parts. Ultrasonic dispersion is used in the mixing and dispersing process, the frequency is 30-50kHz, the maximum power is 500W, and the ultrasonic time is 30-60 minutes; in step three, the stirring speed is 500-3000 rpm, the defoaming agent is 0.1-2 parts, and the static defoaming time is 30-200 minutes.

7. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S5, the base resin is a thermoplastic and / or thermosetting resin; the thermoplastic resin includes polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl alcohol, polystyrene, polyamide, polyimide, and the thermosetting resin includes epoxy resin, phenolic resin, polyurethane.

8. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S5, the dispersant includes one or more of sodium dodecylbenzene sulfonate, stearic acid, fatty acid glyceride, amino acid surfactant, polyvinyl pyrrolidone, and polyoxyethylene ether; in S5, the coupling agent includes one or more of silane coupling agent, titanate, and aluminate coupling agent.

9. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S5, the defoaming agent is one of silicon, paraffin and mineral oil; the viscosity increasing agent includes one or more of polyborosiloxane and carboxymethyl cellulose.

10. The method for preparing a thermal interface material based on a multi-component composite high thermal conductivity filler according to claim 1, characterized in that: In S5, the heat stabilizer includes one or more of stearates, aromatic amine compounds, phosphites, and hydroxylamine compounds, and the stearate is one of calcium stearate, zinc stearate, and barium stearate; the solvent includes one or more of water, ethanol, acetone, N-methylpyrrolidone, dimethylformamide, and dimethyl sulfoxide; in S6, the coating speed is not more than 10 m / min, the coating thickness is 0.03-2.5 mm, and the heating temperature is not higher than 140°C.